La salud mental (en la Argentina) : dos paradigmas en pugna - Croxatto, Guido Leonardo (2012)
In this paper, a critical analysis of the ?disability? concept in the Argentine\ncivil law is made in light of new paradigms within the mental health context which\ntend to re-establish these individuals? (wrongly called the ?handicapped? or ?disabled?)\ndignity and autonomy, it being understood that the disability is more than an\nillness or limitation of the individual (as usually considered); it is a barrier outlined\nby society itself which then, through the law, disables the individual (declares them\ndisabled). It will be held that the disability embodies a legal contradiction. Within\nthis context, a proposal for change is analysed from a new social model (replacing the\nprotective model of the Argentine Civil Code, which has shown that ?protection? is\na vertical model which tends to silence and isolate those who most need to be heard)\nfocused on the full respect for the dignity and autonomy of the individuals resorting to\nmental health services. The role of the temporary guardian in mental disability proceedings\nis analysed, posing the question of whether they should act as the lawyer of such\nindividuals (Kraut) or as an assistant to the judge (Llambías), emphasizing in said cases\nthe vertical (protective) nature of these procedures (which put the legal proceedings\non an equal footing with part of the medical treatment) and, as a result, the isolation\nand muting of the individual who most needs to be heard during the legal proceedings:\nthe alleged ?disabled?. The conclusion is that the civil law must abandon the disability\nconcept because by making individuals disabled it has not ?protected? or ?recovered?\nthe ?disabled?, it has rather isolated, silenced, killed and annulled them as individuals\n(many times, only to protect property). For the law there can no longer be disabled or\nhandicapped people. Only people. It will be demonstrated that the disability concept is\nincompatible with a human rights-based approach